2014
DOI: 10.3415/vcot-14-04-0054
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriostatic effect of equine pure plateletrich plasma and other blood products against methicillin-sensitive Staphylococcus aureus

Abstract: The plasma complement could be one of the most responsible components of the in vitro bacteriostatic effect of P-PRP, P-PRG, LPG and PPP against MSSA. Additionally, P-PRG was the better biomaterial because it had an acceptable bacteriostatic effect and the highest concentration of growth factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 41 publications
(60 reference statements)
2
24
0
Order By: Relevance
“…While some beneficial effects such as anti-infectious properties [69], growth factor content [70] and promotion of chemotaxis, proliferation and differentiation of cells [71] have been attributed to leucocytes they also contribute to a greater acute inflammatory response [29, 72] and to the expression of catabolic factors, e.g. MMPs and IL-1, that may influence tendon healing negatively [27, 73, 74], so that a low leucocyte content seems to be preferable to enhance anabolic effects during tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…While some beneficial effects such as anti-infectious properties [69], growth factor content [70] and promotion of chemotaxis, proliferation and differentiation of cells [71] have been attributed to leucocytes they also contribute to a greater acute inflammatory response [29, 72] and to the expression of catabolic factors, e.g. MMPs and IL-1, that may influence tendon healing negatively [27, 73, 74], so that a low leucocyte content seems to be preferable to enhance anabolic effects during tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…59 Both TGF-b1 and PDGF-BB contained within PRP have been reported to exert bacteriostatic effects against Staphylococcus aureus. 60 Although several of these molecules are recognized for their chemotactic (CCL3, CCL5, and CXCL1) and immune regulatory activity (TGF-b1), evidence suggests they can also act as antimicrobials upon cleavage. 61,62 Staphylococcus aureus is a common pathogen in infected wounds.…”
Section: Prp Antibacterial Propertiesmentioning
confidence: 99%
“…Some authors have empirically supposed that PCs could promote infections, associating them with microbiological culture media and acting as a substrate for the growth of bacteria ( 27 ). More recently, on the contrary to this theory, some evidence would attribute to PCs an inhibitory effect on bacterial growth, although the results cannot be considered definitive yet ( 27 31 ). The antibacterial properties of PCs are supported by some in vitro studies conducted mostly in humans ( 28 , 30 , 32 50 ), but also in horses ( 31 , 51 , 52 ) and rabbits ( 53 ).…”
Section: Introductionmentioning
confidence: 90%
“…More recently, on the contrary to this theory, some evidence would attribute to PCs an inhibitory effect on bacterial growth, although the results cannot be considered definitive yet ( 27 31 ). The antibacterial properties of PCs are supported by some in vitro studies conducted mostly in humans ( 28 , 30 , 32 50 ), but also in horses ( 31 , 51 , 52 ) and rabbits ( 53 ). Systematic reviews of current literature considering in vitro , preclinical, and clinical studies have shown that PCs may have antibacterial properties ( 54 56 ).…”
Section: Introductionmentioning
confidence: 90%